A latitudinal cline in flowering time in Arabidopsis thaliana modulated by the flowering time gene FRIGIDA - Stinchcombe, John R. (National Academy of Sciences, 2004)
A latitudinal cline in flowering time in accessions of Arabidopsis thaliana has been widely predicted because the environmental cues that promote flowering vary systematically with latitude, but evidence for such clines has been lacking. Here, we report evidence of a significant latitudinal cline in flowering time among 70 Northern European and Mediterranean ecotypes when grown under ecologically realistic conditions in a common garden environment. The detected cline, however, is found only in ecotypes with alleles of the flowering time gene FRIGIDA (FRI) that lack major deletions that would disrupt protein function, whereas there is no relationship between flowering time and latitude of origin among accessions with FRI alleles containing such deletions. Analysis of climatological data suggests that late flowering in accessions with putatively functional FRI was associated with reduced January precipitation at the site of origin, consistent with previous reports of a positive genetic correlation between water use efficiency and flowering time in Arabidopsis, and the pleiotropic effects of FRI of increasing water use efficiency. In accessions collected from Southern latitudes, we detected that putatively functional FRI alleles were associated with accelerated flowering relative to accessions with nonfunctional FRI under the winter conditions of our experiment. These results suggest that the ecological function of the vernalization requirement conferred by FRI differs across latitudes. More generally, our results indicate that by combining ecological and molecular genetic data, it is possible to understand the forces acting on life history transitions at the level of specific loci.